Avaliação do Programa de Educação Continuada do CFC pela óptica dos peritos contábeis do Estado de São Paulo - Prado, Marcelo de Almeida (2025)
This study aimed to identify, among accounting professionals registered in the National Registry of Forensic Accountants (CNPC) in the State of São Paulo, the contributions of the Continuing Professional Education Program (PEPC) of the Federal Accounting Council (CFC) to the improvement of forensic work. The research also involved an academic review to support the development of a questionnaire based on the Kirkpatrick Model, which was applied to forensic accountants registered in the CNPC in São Paulo. The responses were analyzed, and the results provide valuable insights into the respondents’ profiles, their participation in CPE activities, the evaluation of PEPC's impact on forensic practice, and areas for improvement. It was found that PEPC plays an important role in the quality of forensic work. This study seeks to contribute to the improvement of CPE activities promoted by the CFC/CRCs System and by other entities, such as associations, unions, and higher education institutions. Future research suggestions include studies that delve deeper into the factors of professional satisfaction with PEPC, identifying essential skills for forensic accountants, and aligning PEPC courses with these skills